A SOCIAL COST BENEFIT ANALYSIS OF “DOOR TO DOOR GARBAGE COLLECTION PROJECT” - Das, Sonashree (The journal of contemporary issues in business and government, 2021)
Waste management is one of the major concerns of the developing countries today. The increase in population and the exploitation of all kinds of natural recourses without the inclusion of sustainable practices have added to generation of solid and hazardous waste endangering living beings and the ecosystem. More or less every country is putting effort to develop and maintain an effective mechanism for managing waste. In India, many states and cities including Assam have undertaken significant steps to address this issue. Sivasagar, a city in Upper Assam has recently joined this endeavor and is on its way of implementing certain projects. This study would focus on Social Cost Benefit Analysis of a project named “Door to Door Garbage Collection” recently implemented by Sivasagar Municipal Board. It is expected that the study would reveal relevant social cost and benefits to be considered while undertaking such kind of projects in developing nations.